From Declarative to Procedural Knowledge: Toward a More Efficient Arabic Teaching in Indonesia - Bakri Ahmed Mohammad Khatir (Islamic University of Indonesia, 2022)
Declarative and procedural knowledge are the two knowledge systems in the second language acquisition process. Declarative knowledge is more prevalent in Indonesia when it comes to the teaching and learning of Arabic. Thus, Arabic education in Indonesia focuses more on knowledge and memorization of grammar. Meanwhile, procedural knowledge is often overlooked. This research aims to present procedural knowledge system as the alternative to transform the Arabic learning in Indonesia. The method used in this research is the descriptive qualitative model. This research found that several language patterns need to be mastered to achieve optimal procedural knowledge. These patterns require appropriate learning strategies. Metacognition is the main key in conducting self evaluation in preparing learning strategies. This article describes ninepatterns in Arabic that should be mastered for activating the learner's procedural knowledge.